Hair Cortisol Is Associated With Social Support and Symptoms in Schizophrenia - Yang, Fuzhong; Cao, Xinyi; Sun, Xiujia; Wen, Hui; Qiu, Jianyin; Xiao, Hua (Frontiers in Psychiatry, 2020)
Introduction: Psychosocial stressors may worsen psychotic symptoms in schizophrenia, while social support could protect against the effects of stress in schizophrenia. Hypothalamus-pituitary-adrenal axis dysfunction has been associated with schizophrenia. Hair cortisol concentrations (HCC) allow assessment of cumulative cortisol secretion over the preceding 3 months. The relationship between HCC, psychosocial stressors, social support and the clinical characteristics of schizophrenia needs to be explored. Methods: 109 schizophrenia patients and 86 healthy controls between the ages of 18 and 60 were enrolled in the study. Three-centimeter samples of hair were collected from the scalp and HCC were measured using ELISA kits. Linear regression and factor analysis were employed to examine the relationship between HCC, childhood trauma, the number of stressful life events (SLE), the amount of social support in the 3 months prior to the hair cortisol assessment and clinical characteristics of schizophrenia. Results: Schizophrenia patients experience more SLE in their lifetime, receive less social support and have lower HCC in the recent 3 months compared to healthy controls. In the schizophrenia patients, HCC are positively associated with the amount of social support and negatively associated with the severity of delusions. The interaction between social support and SLE predicts decreased HCC. Factor analysis shows that a subgroup of schizophrenia patients who experience childhood trauma and SLE are characterized by decreased HCC. Conclusions: Findings indicate social support could be a moderator for the relationship between SLE and HCC which may attenuate the effects of SLE in schizophrenia.